Outsourcing, foreign ownership and productivity: evidence from UK establishment level data - Sourafel Girma; Holger Görg (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2002)
This paper presents an empirical analysis of “outsourcing” using establishment level data for UK manufacturing industries. We analyse an establishment's decision to outsource and the subsequent effects of outsourcing on the establishment's productivity. We compare outsourcing in domestic with foreign-owned establishments. Our empirical results suggest that high wages are positively related to outsourcing, suggesting that the cost saving motive is important. We also find that foreign-owned firms have higher levels of outsourcing than domestic establishments. In the productivity analysis we find that an establishment's outsourcing intensity is positively related to its labour productivity and total factor productivity growth and that this effect is more pronounced for foreign establishments.
Keywords: 330; Outsourcing; Unternehmensentwicklung; Produktivität; Eigentümerstruktur; Verarbeitendes Gewerbe; Großbritannien